Studi Carbon Footprint Untuk Menghitung Emisi CO2 Primer Dari Aktivitas Rumah Tangga Di Wilayah Pengembangan I Kota Pekanbaru - Hiqma Aulia; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Development Area I is for the residential area, trade and service center, and government office center in Pekanbaru City. Development area I is the center of service, which has the potensial as one of the contributors to CO2 emissions into the air. The purpose of this research is to amount of total primary CO2 emissions with carbon footprint method from household activities in Development Area I, Pekanbaru City. The method of this research used IPCC (1996) method to calculation of primary CO2 emissions and using primary data and secondary data, primary data was obtained from surveys and interviews related to fuel use in the household and secondary data was obtained from relevant agencies such as regional maps and demographic data. The result of this research was knew the amount of total primary CO2 emissions from household activities in the Development Area I in Pekanbaru City was about 1.464,80 tons CO2/month. Keywords: Carbon Footprint, Primary CO2 emission, Household, Fossil Fuels.